Histopathological Spectrum of Pigmented Skin Lesions in a Tertiary Care Centre of Nepal - Ranabhat, Sunita; Poudel, Suman; Pun, Gita (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Pigmented skin lesions are defined as altered pigmentation of the skin as well as mucous membrane which can present as flat or raised growth and can be blue, brown, black or grey in color. The main aim of the study was to see the histopathological spectrum of pigmented skin disease and compare the clinical and histopathological diagnoses. Methods It is observational cross-sectional study conducted in the Department of Pathology of Gandaki Medical College and Teaching hospital from January 2022 to December 2022 and 80 cases were included. Results Age of the patient ranged from seven to 89 years and mean ± SD was 49.55 ± 21.73 years. There were 34 (42.6%) males and 46 (57.4%) females with a female: male ratio 1.3:1. The most common site of distribution of pigmented lesions of the skin were face in 44(55%) followed by trunk in 15(18.7%), extremities in 13(16.2%), scalp in 7(8.8%) and genitalia in 1 (1.3%). Histopathological study revealed the most common lesion as melanocytic nevi 14(17%) followed by basal cell carcinoma 11(13.8%), seborrheic keratosis 6(7.6%), Keratoacanthoma 5(6.3%), verrucous epidermal nevus 4(5%) and others cases in few numbers. Clinicopathological agreement was seen in 44 (55%). Conclusions Melanocytic nevi were the most common among the pigmented skin lesion. Other causes of pigmented lesions were due to keratinocytic, vascular and reactive changes. Malignant tumors can sometimes mimic benign lesions. Therefore, histopathological examination remains the gold standard in diagnosing these conditions and provide proper guidance for further management of patients.